The effect of systemic iron status on osteoarthritis: A mendelian randomization study - Ruan, Guangfeng; Ying, Yi; Lu, Shilong; Zhu, Zhaohua; Chen, Shibo; Zeng, Muhui; Lu, Ming; Xue, Song; Zhu, Jianwei; Cao, Peihua; Chen, Tianyu; Wang, Xiaoshuai; et al. (Frontiers in Genetics, 2023)
Objective: To assess the causal effect of systemic iron status by using four biomarkers (serum iron; transferrin saturation; ferritin; total iron-binding capacity) on knee osteoarthritis (OA), hip OA, total knee replacement, and total hip replacement using 2-sample Mendelian randomization (MR) design. Methods: Three instrument sets were used to constructed the genetic instruments for the iron status: liberal instruments (variants associated with one of the iron biomarkers), sensitivity instruments (liberal instruments exclude variants associated with potential confounders), and conservative instruments (variants associated with all four iron biomarkers).Summary-level data for four OA phenotypes, including knee OA, hip OA, total knee replacement, and total hip replacement were obtained from the largest genome-wide meta-analysis with 826,690 individuals. Inverse-variance weighted based on the random-effect model as the main approach were conducted. Weighted median, MR-Egger, and Mendelian randomization pleiotropy residual sum and outlier methods were used as sensitivity MR approaches. Results: Based on liberal instruments, genetically predicted serum iron and transferrin saturation were significantly associated with hip OA and total hip replacement, but not with knee OA and total knee replacement. Statistical evidence of heterogeneity across the MR estimates indicated that mutation rs1800562 was the SNP significantly associated with hip OA in serum iron (odds ratio, OR=1.48), transferrin saturation (OR=1.57), ferritin (OR=2.24), and total-iron binding capacity (OR=0.79), and hip replacement in serum iron (OR=1.45), transferrin saturation (OR=1.25), ferritin (OR=1.37), and total-iron binding capacity (OR=0.80). Conclusions: Our study suggest that high iron status might be a causal factor of hip OA and total hip replacement where rs1800562 is the main contributor.